Butterflies Diversity in Brawijaya University, Veteran, Jakarta and Velodrom Green Open Space - Ayu Raisa Khairun Nisa'; Minahanggari Mukti; Muhammad Fathoni Hamzah; Arif Mustakim; Zainal Abidin (Journal of Tropical Life Science, 2013)
Butterflies have some roles in environmental as pollinator and bioindicator. Habitat is one of important factor to support butterflies growth. The aim of this research was to describe butterflies diversity in some green open spaces in Malang. Direct observations of butterflies diversity, vegetation structures and abiotic factors in Brawijaya University, Veteran, Jakarta and Velodrom Green Open Space were conducted on June 2012. Sampling was took place in each sites using cruising method in three times observation at 07.00, 11.00 a.m. and 3.30 p.m . Data were analyzed by statistical descriptive using Microsoft Excel 2007 and PAST. The result showed that butterflies composition in all sites dominated by Delias sp., Leptosia nina and Eurema venusta. The diversity index of all sites showed moderate rank that indicate communities equilibrium in environment was still good. In this case, Velodrom Green Open Space has the highest one of diversity index, it was about 2,199. Brawijaya University and Jakarta Green Open Space have a high similarity index based on Morisita Index. The highest abundance of butterflies was observed at 11.00-12.30 a.m. Delias sp. and Leptosia nina has temporal spread all day long, while Eurema venusta just in day light.